The Students’ Perspective of Using Instagram as a Writing Assignment Platform - Tenia Ramalia (J-SHMIC : Journal of English for Academic, 2021)
This study aimed to find out the students’ perspective of using Instagram as a writing assignment platform. Using a qualitative research method, this study involved the students of the 2nd semester in English Department Universitas Islam Syekh-Yusuf Tangerang. There were 61 students in writing class who were involved as the participants. It used the technique of survey with open-ended questionnaire as the instrument of data collection The results show that almost all students have positive perspective towards Instagram as a writing assignment platform. The participants found out that Instagram was fun, easy, and effective media to be used in doing writing assignment. Although, there were also some barriers in using it such as, bad internet network and privacy issue. It can be concluded that, Instagram can be one of useful teaching media, especially for writing, as long as it is used and supervised appropriately.